AUDIT ENERGI UNTUK PENCAPAIAN PENGHEMATAN PENGGUNAAN ENERGI LISTRIK DI PT. GRAHA SARANA DUTA II DENPASAR - Oktavia Ginting, Sylvi; Manuaba, Ida Bagus Gede; Maharta Pemayun, A A Gede (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i01.p4, 2022)
Energy audit is a technique used to determine the amount of energy use in a building and to find various energy-saving solutions or opportunities. In this study, the energy audit was conducted at PT. Graha Sarana Duta II Denpasar which is located on Jl. Serma Gede No. 13, Dauh Puri Klod, Denpasar. Based on the existing conditions, the level of Energy Consumption Intensity (IKE) obtained before the audit was carried out was 245.22 kWh/m2/year or 20.43 kWh/m2/month which according to ESDM No. 13/2012, Air-conditioned buildings are in the wasteful category. In this study, the energy audit focuses on the lighting system and air conditioning system. The method used in this research is to calculate and analyze the consumption of electrical energy in the lighting system and air conditioning system. After doing the research, it can be seen the energy saving opportunities (PHE) in PT. Graha Sarana Duta II Denpasar by replacing the TL and SL lamps using LED lamps and requiring room users to turn off the air conditioner when the room is not in use, the result is savings 11,4% in electrical energy use, where the IKE after the audit is 18.1 kWh/m2/month. The office can also save the cost of using electrical energy, which is Rp. 3,170,394,- every month.